Odpowiedzi

Najlepsza Odpowiedź!
2010-01-03T11:51:19+01:00
A.) (1 - sinα)(1 + tgα cosα) = sin²(90°-α)
L = (1 - sinα)(1 + sinα/cosα * cosα) = (1 - sinα)(1 + sinα) = 1 - sin²α = cos²α = cosα - sin²(90° - α) + sin²(90° - α) = (cosα - sin(90° - α))(cosα + sin(90° - α)) + sin²(90° - α) = (cosα - cosα)(cosα + cosα) + sin²(90° - α) = 0*2cosα + sin²(90° - α) = sin²(90° - α) = P

b.)(1 + cosα)(1 - ctgα sinα) = cos²(90°- α)
L = (1 + cosα)(1 - ctgα sinα) = (1 + cosα)(1 - cosα/sinα * sinα) = 1 - cos²α = sin²α = sin²α - cos²(90°- α) + cos²(90°- α) = (sinα - cos(90° - α))(sinα + cos(90° - α)) + cos²(90°- α) = (sinα - sinα)(sinα + sinα) + cos²(90°- α) = 0*2sinα + cos²(90°- α) = cos²(90°- α) = P

jeżeli czegoś z tego nie rozumiesz pisz na pw